Pan-African imprint on the early mid-proterozoic Richtersveld and Bushmanland sub-provinces near Eksteenfontein, Namaqualand, Republic of South Africa - Booth, Peter William King (Department of Geological Sciences, 2017)
The present investigation examines the relationship between the Proterozoic Richtersveld and Bushmanland Subprovinces in the westernmost part of the Namaqua Province, near Eksteenfontein, Republic of South Africa. There is a controversy about this relationship because isotopic data contrast with field evidence. On a regional scale the Richtersveld Subprovince is separated from the Bushmanland Subprovince by the northward-dipping Groothoek Thrust. North of the thrust the Richtersveld Subprovince is comprised of low grade volcano/ plutonic rocks of the Vioolsdrif Terrane and medium grade volcano sedimentary sequences of the Pella Terrane. Medium grade rocks of the Steinkopf Terrane (Bushmanland Subprovince) lie immediately south of the thrust. Late Proterozoic strata of the Stinkfontein Formation (Gariep Group) overlie the Namaqua Province in the west; Cambrian Nama Group outliers occur east of the Stinkfontein Formation. Isotopic data show that lithologies of the Richtersveld Subprovince formed between 2000 - 1730 Ma, whereas those of the Bushmanland Subprovince are younger. It is not clear whether the Namaqua metamorphic imprint (at 1200 - 1100 Ma), which is manifest in terranes south of the Groothoek Thrust, extended as far as the Vioolsdrif Terrane in the north. Early Proterozoic structural and metamorphic imprints are inferred to have been obliterated during this event. The westernmost part of the Namaqua Province was overprinted for a distance of 100 km from the coast, during the Pan-African event at 700 Ma and 500 Ma. An area measuring nearly 500 km2 , traversing the western extremity of the boundary between the Richtersveld and Bushmanland Subprovinces was mapped on a scale of 1:36,000. Field mapping was carried out with the aid of aerial photographs, whereas laboratory techniques included map compilation, structural analysis, X-ray diffractometry, geochemical (XRF) and electron microprobe analyses. Supracrustal units of the Richtersveld Subprovince are composed of quartzo-feldspathic gneisses, schists, and minor meta-pelites. Supracrustals of the Bushmanland Subprovince are less diverse than those of the Richtersveld Subprovince and have a disconformable relationship with them. Most intrusive rock-types are thick granitic sheets, except the Early Proterozoic Vioolsdrif Granodiorite which forms part of a batholithic pluton in the north. The Sabieboomrante adamellite gneiss, Kouefontein granite gneiss and Dabbieputs granite gneiss could not be correlated with lithologies commonly occurring in the Richtersveld and Bushmanland Subprovinces. They have been given the new rock names. Mafic and ultramafic rocks of the Klipbok complex occur along the strike of the Groothoek Thrust. They form part of the Richtersveld Subprovince.